ANALISIS MANAJEMEN RISIKO SISTEM INFORMASI DALAM PENGGUNAAN APLIKASI E-PURCHASING BERBASIS ISO 31000 (STUDI KASUS TOKO ASHA) - I Wayan Ady Juliantara; Wayan Eka Ariawan; I Nyoman Ariana Guna (Universitas Tabanan, 2025)
The development of information technology has driven digitalization in various sectors, including in the procurement of government goods and services through the E-purchasing system. ASHA Store is one of the business actors that utilizes the e-Catalog and Mbizmarket platforms in carrying out transaction processes with government agencies. However, in its implementation, the information system used also creates various operational risks that can disrupt the smooth running of the business. This study aims to analyze the risk management of the information system implemented by ASHA Store using the ISO 31000:2018 framework. The method used is a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results of the study showed that there were ten main risks identified, including internet connection disruptions, inaccessible applications, and delays in updating product data and shipping goods. These risks were then analyzed based on their likelihood and impact, so that mitigation priorities were obtained. Control measures were carried out with strategies such as increasing staff training, providing backup networks, and implementing dual authentication and data backup SOPs. By conducting periodic evaluation and monitoring, the implementation of ISO 31000-based risk management has proven effective in helping ASHA Store identify, analyze, and control information system risks systematically and sustainably.